Influence of Managerial Styles on Career Satisfaction and Occupational Stress: The Mediating Role of Followership Styles and the Interaction Effects of Organizational Citizenship Behavior of Three Star Hotels - Olivar, Kiven G.; Ocio, Ritchard L.; Sitier, Noah James S. (Archives of Business Research, 2022)
The aim of the study was to determine the mediating effect of followership styles and the interaction effects of organizational citizenship behavior and influence of managerial styles on career satisfaction and occupational stress of 300 employees of three star hotels in Davao City, Philippines. This study employed descriptive correlation as part of a non-experimental design. The statistical techniques employed were mean, Pearson r, regression technique, and Medgraph employing Sobel z-test. Research finding revealed that the Sobel test depicted that the Followership Styles and the Interaction Effects of Organizational Citizenship Behavior (mediator) significantly carries the influence of Managerial style (IV )to the Career Satisfaction and Occupational Stress (DV).